Exploring the role of cultural values, trust and empathy on satisfaction: Research on hotel customers - Aybike Tuba Özden; Olcay Özışık Yapıcı; Mehdi Korjani (Tourism)
Hotels that serve customers having different cultural values should improve their service capabilities to achieve customer satisfaction. This study researches how empathy, trust and cultural values affect hotel customer satisfaction and looks at the combinations of these components that lead to high customer satisfaction. The current literature on Hofstede’s five-dimensional cultural values, cognitive and affective dimensions of empathy, trust and customer satisfaction were used to develop the research model and present recommendations. To ensure cultural diversity, a face-to-face survey was administered to 553 tourists from six countries. The data obtained were evaluated using partial least squares structural equation modelling and fuzzy set qualitative comparative analysis (fsQCA). According to the results, the effects of hotel customers’ empathy levels on their satisfaction occur through their trust in the business. The fsQCA revealed combinations of cultural values, empathy and trust that would generate high levels of satisfaction. The present study contributes to the relevant literature by addressing the relatively under-emphasized components that ensure that hotel customers are highly satisfied.